2019
DOI: 10.3344/kjp.2019.32.2.105
|View full text |Cite
|
Sign up to set email alerts
|

Small dose of naloxone as an adjuvant to bupivacaine in intrapleural infiltration after thoracotomy surgery: a prospective, controlled study

Abstract: Background Severe pain always develops after thoracotomy; intrapleural regional analgesia is used as a simple, safe technique to control it. This study was performed to evaluate whether a small dose of naloxone with local anesthetics prolongs sensory blockade. Methods A prospective, randomized double-blinded controlled study was conducted on 60 patients of American Society of Anesthesiologists statuses I and II, aged 18 to 60 years, scheduled for unilateral thoracotomy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The authors reported that naloxone increased the sensory block duration by approximately 3 h. Recovery of the sensory block was slower in the naloxone mixed group than in the control group. Similarly, Amer and Omara [ 14 ] showed that a low dose of naloxone prolonged intrapleural infiltration after surgery involving thoracotomy. Based on the previous studies, we applied it for the first time to the femoral nerve block with a low dose of naloxone to a ropivacaine solution.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The authors reported that naloxone increased the sensory block duration by approximately 3 h. Recovery of the sensory block was slower in the naloxone mixed group than in the control group. Similarly, Amer and Omara [ 14 ] showed that a low dose of naloxone prolonged intrapleural infiltration after surgery involving thoracotomy. Based on the previous studies, we applied it for the first time to the femoral nerve block with a low dose of naloxone to a ropivacaine solution.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies examining the use of naloxone to alleviate pain when added in small amounts to LA in various neural blockade procedures have been published [ 11 14 ]. Movafegh et al [ 12 ] studied the effect of appending a low dose of naloxone to a lidocaine solution for axillary blockade and reported that this combination prolongs motor and sensory blockade, with a significantly increased interval to the first sensation of postoperative pain in the naloxone group.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations